Indonesian EFL Teachers’ Professional Development: Views and Current Practices - Dewi, Utami; Fithriani, Rahmah; Berutu, Hotma (Indonesian Research Journal in Education |IRJE|, 2024)
Teachers play a critical role when it comes to impacting student achievement. Consequently, the matter of teacher quality is currently being tackled through the implementation of professional development (PD) initiatives. PD in English as a foreign language (EFL) teaching and learning context has gained burgeoning attention in the last decade. However, it is not known how Indonesian EFL teachers perceive and practice PD for their professional development. The objective of this research was to investigate the viewpoints of EFL teachers in Indonesia towards the importance of professional development (PD) and ascertain their existing PD practices, if any. A total of 70 teachers participated in this study by completing the survey, with 37 of them subsequently invited to participate in the forum group discussion (FGD) on a voluntary basis.  The analysis of the collected data revealed that the participants perceived PD as significant for their professional development in three areas: knowledge, pedagogy, and language proficiency. Conversely, the findings also reveal a low degree of participation in professional development activities (PDAs), despite their common engagement in these activities. This study concludes by highlighting the significance of addressing certain areas that require particular attention to effectively support teachers in their continuous professional development endeavors.